From Anxiety to Boredom—The Transformation of Phenomenology of Affectivity from Heidegger’s De-subjectification Perspective - Lu, Zhizhe (Journal of Social Science and Humanities, 2024)
In Being and Time, Heidegger argues that anxiety can enable individuals to free themselves from the they or the subject and thus individualise themselves. However, this discussion can lead to the misunderstanding that, by shaking off the identity of a general subject, Dasein becomes an individual subject. Then Heidegger's critique of the philosophy of subjectivity would not only be unsuccessful but would also be somewhat extreme. In the face of this danger, Heidegger replaces the basic affectivity of anxiety with boredom. By analysing boredom, Heidegger achieves the goal of de-subjectification.